Positive free speech : rationales, methods and implications - Kenyon, Andrew T.; Scott, Andrew, 1974- (Oxford ; Hart, 2020)
"Freedom of expression is generally analysed as a bare liberty that should not be constrained by state action. Underpinning rationales for freedom of speech very often imply, however, that the concept also has important positive aspects, and that to be truly 'democratic' the modern polity requires more than negative freedom. In contemporary conditions, this understanding of free speech raises matters such as media diversity or pluralism, the concept of voice and access to the public sphere, access to information, and the need to rethink the audience in relation to public speech. Whether securing positive free speech is a matter of politics or of law, a task for legislatures or for courts, is an open question. On one level, any programme of inculcating positive dimensions of free speech might be understood as inherently polycentric and hence political in character. Yet, a number of Northern European jurisdictions evince enhanced legal recognition for the principle. The aim of this collection of papers is to interrogate the rationales of positive free speech, to consider the political and juridical methods by which it has or may be more fully reflected in the modern state, and to consider the range of practical contexts in which its valorisation has or would have significant implications. The contributors are drawn from an array of European and international jurisdictions. They include academic lawyers, sociologists, and political scientists"--
Complicating Freedom : Investigating Positive Free Speech / Andrew T Kenyon -- Providing a Platform for Speech : Possible Duties and Responsibilities / -- Thomas Gibbons -- Positive Protection for Speech and Substantive Political Equality / Jacob Rowbottom -- The Access to Information Dimension of Positive Free Speech / Andrew Scott and Abbey Burke -- Promoting Civic Discourse : A Form of Positive Free Speech under the Constitution of Ireland? / Eoin Carolan -- Th e State of Affairs of Freedom : Implications of German Broadcasting Freedom / Andrew T Kenyon -- The Collective Speech Rights of Minorities / Sally Broughton Micova -- The Positive Right to Freedom of Expression and Party Anonymity in Legal Proceedings / Merris Amos -- Positive Free Speech and Public Access to Courts / Judith Townend -- Hiding the Truth in the Shadow of the Law? : Addressing the Misuse of Confidentiality Clauses in Public Authority Contracts / Andrew Scott -- Speaking and Governing through Freedom of Access to Environmental -- Information / Mélanie Dulong de Rosnay and Laura Maxim
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Freedom of speech -- Europe; Entertainment & media law; Electronic books